Perancangan Aplikasi Kuis (VOCANETIC) untuk SMK Jurusan RPL menggunakan Microsoft Visual Studio - Saskia Widya Aini; Winda Ayu Amelia; Hanydhar Rose Manicha; Nisa Dwi Septiyanti; Rizky Basatha (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
Rapid advances in Information Technology (IT) in the 21st century have significantly transformed educational practices, particularly in vocational high schools (SMK) specializing in Software Engineering (RPL). Traditional learning media, such as textbooks, static slides, and lectures, often fail to provide an interactive learning experience, limiting students’ engagement and reducing the effectiveness of knowledge retention. To overcome this challenge, this study focuses on developing and validating an interactive quiz application called VOCANETIC, designed as an innovative learning aid for SMK RPL students. The research uses a Research and Development (R&D) approach, emphasizing the stages of product development, expert validation, and feasibility assessment. VOCANETIC is developed using VB.NET in the Microsoft Visual Studio environment, and MySQL is employed for efficient data management and storage. The application features interactive quizzes, real-time feedback, and user-friendly interfaces to enhance student engagement and motivation. Based on evaluation and analysis by expert validators, VOCANETIC meets the “Proper” feasibility criteria, demonstrating usability, interactivity, and educational effectiveness. The results indicate that VOCANETIC is capable of supporting active learning, improving students’ understanding of software engineering concepts, and providing an effective platform for self-assessment and practice. In conclusion, the VOCANETIC application is proven to be a valid, reliable, and practical tool that can be implemented as an interactive learning medium in SMK RPL, offering an innovative approach to facilitate student learning and engagement in the digital era.